Student‟s Perception of Online Learning in Pandemic - Winda Purnama Sari; Diana Pramesti; Adevia Indah Kusuma (PROCEEDING UMSURABAYA, 2020)
Abstract. This study aimed to explore the perceptions of student‘s in an implementation ofonline learning in pandemic era. This new phenomenon where currently the educators and students are grappling with the idea, innovation, problem solving skills to implementation and adaptation. Especially, with the development of ICT and relative exposure of students to it, this study examines student‘s perception about online learning which help in a newer teaching and learning experiences on the campus. The Ministry of Education and Culture recommends learning from home using online learning. Primary Teacher Education Program Study in STKIP Muhammadiyah Bangka Belitung (STKIP MBB) has been implemented online learning to use the LMS, social media, and some application to supported learning process. This was a descriptive strudy involved an analysis of survey of student regarding their perception on online learning. Technique the sample collection usedsimple random sampling on 1st, 2nd, and 3rd years primary teacher education in STKIP MBB about 150 student‘s. The data were collected through questionnaires of the student‘s perception of online learning. The data analysis used descriptive analysis. The result of this study was student‘s perception of online learning to use varied media or application in the course has a somewhat good category (38,75%) for implementation and the student‘s suggestion to start What‘s App, Google Meet or Zoom Application.